Ritual Kematian Rambu Solo' sebagai Cermin Keberagaman Budaya Toraja - Hamdiyah, Nisa Nurul; Alimudin, Ahmad Rizki; Musdalipah, Lula (IAIN Syekh Nurjati Cirebon, 2024)
Toraja is one of Indonesia's regions known for its rich cultural diversity, particularly in its traditional ceremonies and customs. One of the most significant traditions is the death ritual known as Rambu Solo'. This ritual not only serves as the final respect for the deceased but also symbolizes the social status and cultural identity of the Torajan people. Besides its deep spiritual significance, Rambu Solo' plays a vital role in strengthening social bonds within the community through a process filled with symbolic meanings. This tradition has endured for centuries, even as the Torajan society faces the challenges of modernization, which is increasingly altering their social and economic structures.This research employs a qualitative approach with library research methodology and a descriptive-analytic method. The study aims to analyze how the history and cultural diversity of Toraja, specifically in the practice of Rambu Solo', have evolved over time. The findings reveal that Rambu Solo' has undergone a transformation in its values amid the pressures of the global economy and modernization.. The commodification of this ritual is also highlighted, with the tourism industry playing a significant role in sustaining the tradition while simultaneously presenting challenges for the Torajan people in preserving the spiritual values inherent in the ritual. This study provides a comprehensive view of the social and cultural dynamics within the Rambu Solo' ceremony and the challenges faced by the Torajan community in maintaining their traditions in the modern era.